2018
DOI: 10.1111/jfb.13542
|View full text |Cite
|
Sign up to set email alerts
|

Across rather than between river genetic structure in Atlantic salmon Salmo salar in north‐east Scotland, UK: potential causes and management implications

Abstract: The aim of this study was to examine the genetic structuring, based on c. 4300 single nucleotide polymorphic markers, of juvenile Atlantic salmon Salmo salar sampled from 11 rivers in north-east Scotland, which form part of a radial drainage system. Within this area, sites in the upper mountainous and lower coastal sections of the different rivers were more closely related than sites from the upper and lower sections of the same river. Differentiation between fish from upper and lower sections was related to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…This is however within typical Atlantic salmon straying rates between watersheds, estimated from other studies (3-10%, Stabell 1984;Jonsson et al 2003;Keefer and Caudill 2014). Cauwelier et al (2018b) examined 11 Atlantic salmon rivers in Scotland and observed a similar pattern of upstream-downstream rather than among-river genetic structuring, associated with exceptionally high rates of straying between rivers (27.4%). This suggests an alternative hypothesis that factors independent of the bifurcation are maintaining the parallel upstream-downstream structure in the Kalix and Tornio.…”
Section: Genetic Homogeneity Between Riverssupporting
confidence: 74%
“…This is however within typical Atlantic salmon straying rates between watersheds, estimated from other studies (3-10%, Stabell 1984;Jonsson et al 2003;Keefer and Caudill 2014). Cauwelier et al (2018b) examined 11 Atlantic salmon rivers in Scotland and observed a similar pattern of upstream-downstream rather than among-river genetic structuring, associated with exceptionally high rates of straying between rivers (27.4%). This suggests an alternative hypothesis that factors independent of the bifurcation are maintaining the parallel upstream-downstream structure in the Kalix and Tornio.…”
Section: Genetic Homogeneity Between Riverssupporting
confidence: 74%
“…In our case, cross-watershed gene flow was found in two areas, both closely adjacent tributaries at the same elevation. This finding is reminiscent of a recent study of Atlantic salmon (Salmo salar), where fish located at the same elevation but in different rivers were more related to each other than to fish in the same river but at a different elevation (Cauwelier, Stewart, Millar, Gilbey, & Middlemas, 2018). Uniquely in our study, the two cross-watershed genetic linkages seemed to have occurred on different timescales (historical and contemporary) in different parts of the watershedsneither of which are associated with any known human-mediated introductions.…”
Section: Discussionsupporting
confidence: 81%
“…This will require new screening panels and data baselines to be developed, ideally encompassing adaptively relevant and life‐history markers (e.g. Cauwelier et al., 2018). Encompassing markers such as Vgll3, six6 , also offers the possibility of comparing ocean migration and distribution patterns for different sea age phenotypes (Aykanat et al., 2020; Ayllon et al., 2015; Barson et al., 2015), enhancing understanding stock‐specific responses to environmental change.…”
Section: Discussionmentioning
confidence: 99%